Politics in the interest of capital: A not-so-organized combat - Cornelia Woll (Max Planck Sciences Po Center on Coping with Instability in Market Societies (MaxPo), 2015)
The rise in inequality has been explained with reference to organized groups and the lobbying of the financial sector. This article argues that the image of politics as organized combat is contradicted by empirical evidence on lobbying in the United States, and does not travel well to Europe. The power of finance does not operate through organized political influence. Rather, politics in the interest of capital unfolds as a structural feature of advanced economies over time. Tellingly, at the height of the financial crisis, one of the most promising strategies of institutions seeking government support was not organizing for combat, but collective inaction. Our challenge, then, is to explain how the power of finance has built up and is playing out in creating inequality. A more structural, less agency-focused perspective highlights how the rise of finance has been supported by actors that few would accuse of being finance-friendly, such as the European center-left parties and consumers. Reconceptualizing the power of finance has important implications for political solutions to rising inequality.
Keywords: 330